2013
DOI: 10.1097/mpg.0b013e318295fc65
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Mucosal Involvement Without Amyloidosis in Children With Familial Mediterranean Fever

Abstract: In this report, we described 11 patients who presented with gastrointestinal symptoms and eventually diagnosed as having FMF. Gastrointestinal mucosal involvement without amyloidosis is documented by endoscopic and histopathologic investigations in these patients. We concluded that mucosal involvement of the gastrointestinal tract may be attack-related manifestations in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 7 publications
(8 reference statements)
1
17
0
1
Order By: Relevance
“…2 Although only a few endoscopic findings have been reported, colonoscopy revealed hyperemia, fragility, and patchy ulcerations with white exudate in the large intestinal mucosa. 3 To our knowledge, this case report is the first study to describe observations for the small intestine, which, because they are similar to the findings for the large intestine described previously, indicate that CE and DBE are useful in the diagnosis of FMF.…”
Section: Answer To the Clinical Challenges And Images In Gi Question:supporting
confidence: 83%
“…2 Although only a few endoscopic findings have been reported, colonoscopy revealed hyperemia, fragility, and patchy ulcerations with white exudate in the large intestinal mucosa. 3 To our knowledge, this case report is the first study to describe observations for the small intestine, which, because they are similar to the findings for the large intestine described previously, indicate that CE and DBE are useful in the diagnosis of FMF.…”
Section: Answer To the Clinical Challenges And Images In Gi Question:supporting
confidence: 83%
“…The only endoscopic investigation aiming to detect FMF-related gastrointestinal lesions was reported in a small pediatric cohort by Gurkan et al [9]. They showed colonic inflammation and multiple gastric aphthous ulcerations without amyloid infiltration by gastroscopy and colonoscopy in 11 out of 36 pediatric FMF patients with gastrointestinal symptoms, and they concluded that mucosal involvement of the gastrointestinal tract may be attack-related manifestations in these patients.…”
Section: Discussionmentioning
confidence: 95%
“…But these procedures may only help clinical assessments during diagnosis of FMF . Furthermore, FMF patients had nonspecific findings in screening tests . However, up to now, these have not been given as much weight as clinical features.…”
Section: Discussionmentioning
confidence: 99%